Did you hear that? The role of stimulus similarity and uncertainty in auditory change deafness - Dickerson, Kelly; Gaston, Jeremy R. (Frontiers in Psychology, 2014)
Change deafness, the auditory analog to change blindness, occurs when salient and behaviorally relevant changes to sound sources are missed. Missing significant changes in the environment can have serious consequences, however, this effect, has remained little more than a lab phenomenon and a party trick. It is only recently that researchers have begun to explore the nature of these profound errors in change perception. Despite a wealth of examples of the change blindness phenomenon, work on change deafness remains fairly limited. The purpose of the current paper is to review the state of the literature on change deafness and propose an explanation of change deafness that relies on factors related to stimulus information rather than attentional or memory limits. To achieve this, work on across several auditory research domains, including environmental sound classification, informational masking and change deafness are synthesized to present a unified perspective on the perception of change errors in complex, dynamic sound environments. We hope to extend previous research by describing how it may be possible to predict specific patters of change perception errors based on varying degrees of similarity in stimulus features and uncertainty about which stimuli and features are important for a given perceptual decision.